Dopamine Receptors and Groups I and II mGluRs Cooperate for Long-Term Depression Induction in Rat Prefrontal Cortex through Converging Postsynaptic Activation of MAP Kinases - Otani, Satoru (J Neurosci, 1999)
Tetanic stimuli to layer I–II afferents in rat prefrontal cortex induced long-term depression (LTD) of layer I–II to layer V pyramidal neuron glutamatergic synapses when tetani were coupled to bath application of dopamine. This LTD was blocked by the following metabotropic glutamate receptor (mGluR) antagonists coapplied with dopamine: (S)-α-methyl-4-carboxyphenylglycine (MCPG; group I and II antagonist), (RS)-1-aminoindan-1,5-dicarboxylic acid (AIDA; group I antagonist), or (RS)-α-methylserine-O-phosphate monophenyl ester (MSOPPE; group II antagonist). This suggests that the dopamine-facilitated LTD requires synaptic activation of groups I and II mGluRs during tetanus. LTD could also be induced by coupling tetani to bath application of groups I and II mGluR agonist (1S,3R)-1-aminocyclopentane-1,3-dicarboxylic acid (1S,3R-ACPD). In the next series of experiments, coapplication of dopamine and 1S,3R-ACPD, but not application of either drug alone, consistently induced LTD without tetani or even single test stimuli during drug application, suggesting that coactivation of dopamine receptors and the mGluRs is sufficient for LTD induction. Immunoblot analyses with anti-active mitogen-activated protein kinases (MAP-Ks) revealed that D1 receptors, D2 receptors, group I mGluRs, and group II mGluRs all contribute to MAP-K activation in prefrontal cortex, and that combined activation of dopamine receptors and mGluRs synergistically or additively activate MAP-Ks. Consistently, LTD by dopamine + 1S,3R-ACPD coapplication, as well as the two other forms of LTD (LTD by dopamine + tetani and LTD by 1S,3R-ACPD + tetani), was blocked by bath application of MAP-K kinase inhibitor PD98059. LTD by dopamine + 1S,3R-ACPD coapplication was also blocked by postsynaptic injection of synthetic MAP-K substrate peptide. Our results suggest that dopamine receptors and groups I and II mGluRs cooperate to induce LTD through converging postsynaptic activation of MAP-Ks.